Advances on Greener Asymmetric Synthesis of Antiviral Drugs via Organocatalysis - Everton M. da Silva; Hérika D. A. Vidal; Arlene G. Corrêa (MDPI AG, 2021)
Viral infections cause many severe human diseases, being responsible for remarkably high mortality rates. In this sense, both the academy and the pharmaceutical industry are continuously searching for new compounds with antiviral activity, and in addition, face the challenge of developing greener and more efficient methods to synthesize these compounds. This becomes even more important with drugs possessing stereogenic centers as highly enantioselective processes are required. In this minireview, the advances achieved to improve synthetic routes efficiency and sustainability of important commercially antiviral chiral drugs are discussed, highlighting the use of organocatalytic methods.